Risk factors for the development of pneumonia in acute psychotropic drugs poisoning - Vučinić Slavica (Vojnosanitetski Pregled)
Background/Aim. Pneumonia is the most frequent complication in acute psychotropic drugs poisoning, which results in substantial morbidity and mortality, but which also increases the costs of treatment. Risk factors for pneumonia are numerous: age, sex, place of the appearance of pneumonia, severity of underlying disease, airway instrumentation (intubation, reintubation, etc). The incidence of pneumonia varies in poisoning caused by the various groups of drugs. The aim of this study was to determine the incidence and risk factors for pneumonia in the patients with acute psychotropic drugs poisoning. Methods. A group of 782 patients, out of which 614 (78.5%) with psychotropic and 168 (21.5%) nonpsychotropic drug poisoning were analyzed prospectively during a two-year period. The diagnosis of pneumonia was made according to: clinical presentation, new and persistent pulmonary infiltrates on chest radiography, positive nonspecific parameters of inflammation, and the microbiological confirmation of causative microorganisms. To analyze predisposing risk factors for pneumonia, the following variables were recorded: sex, age, underlying diseases, endotracheal intubation, coma, severity of poisoning with different drugs, histamine H2 blockers, corticosteroids, mechanical ventilation, central venous catheter. The univariate analysis for pneumonia risk factors in all patients, and for each group separately was done. The multivariate analysis was performed using the logistic regression technique. Results. Pneumonia was found in 94 (12.02%) of the patients, 86 of which (91.5%) in psychotropic and 8 (8.5%) in nonpsychotropic drug poisoning. In the psychotropic drug group, pneumonia was the most frequent in antidepressant (47%), and the rarest in benzodiazepine poisoning (3.8%). A statistically significant incidence of pneumonia was found in the patients with acute antidpressant poisoning (p < 0.001). Univariate analysis showed statistical significance for the following parameters: sex (p < 0.05), chronic alcohol intake (p < 0.05), underlying diseases (p < 0.01), central venous catheter (p < 0.05) vasopressors (p < 0.05), coma (p < 0.001), H2 blockers (p < 0.001) and corticosteroids (p < 0.001). The multivariate analysis retained endotracheal intubation and antidepressant drug poisoning as an independent risk factor for pneumonia. Conclusion. Using univariate and multivariate analysis, risk factors for developing pneumonia were disclosed. Some of these factors may be modified by simple medical procedures, thus the incidence and mortality rate of pneumonia in drug poisoning might be substantially reduced.